2012
DOI: 10.1103/physreve.86.051704
|View full text |Cite
|
Sign up to set email alerts
|

Doping the nematic liquid crystal 5CB with milled BaTiO3nanoparticles

Abstract: The simple nematic mesogen 5CB was doped with milled BaTiO 3 nanoparticles and investigated with x-ray scattering. Doping with BaTiO 3 nanoparticles of 9 nm in diameter led to the formation of crystallites. These crystallites precipitated and formed a wax-like nanodispersion of 5CB and nanoparticles which led to intense x-ray scattering signals characteristic for a multilayer structure. Surprisingly, the multilayers possess unusual interlayer spacing which cannot be explained by simple smectic order of the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…6,[14][15][16][17][18][19][20][21][22] In addition to the size, the nanoparticle surface properties are also crucial for the manifestation of a well dispersed medium. Surface modification of NPs has been mainly been employed to achieve long-term stability of NPs in the LC medium and to smoothen director distortions around NPs, 23 thus reducing the cost of elastic energy.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…6,[14][15][16][17][18][19][20][21][22] In addition to the size, the nanoparticle surface properties are also crucial for the manifestation of a well dispersed medium. Surface modification of NPs has been mainly been employed to achieve long-term stability of NPs in the LC medium and to smoothen director distortions around NPs, 23 thus reducing the cost of elastic energy.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…For simplicity the intrinsic anisotropy of TiO 2 was neglected. The lattice constant was taken equal to the larger (average) intermolecular distance in the two materials = ( ) a 2 nm [40,41]. In a possible experiment, the director of the liquid crystal can be anchored by a rubbed polymer layer [18,42,43], such that the preferred molecular orientation is parallel to the interface a p » ( ) 2 (see figure 9).…”
Section: Nematic Fluidsmentioning
confidence: 99%
“…Doping with nanoparticles can change the performance characteristics of LCs, such as electro-optic and dielectric properties, memory effect, and phase behavior. Various types of nanoparticles such as metallic [9], semiconducting [10], ferroelectric [11,12], carbon nano-tubes [13,14], dielectric and insulating [15][16][17][18][19] have been developed in recent years to realize LC nanocolloids. Several reports [20][21][22] have shown that doping of a nematic LC with small amounts of nanoparticles affects the properties of nematic LC such as the decrease of threshold and switching voltages, and switching time of the device.…”
Section: Introductionmentioning
confidence: 99%